Hittite Vocabulary: An Anatolian Appendix to Buck's Dictionary of Selected Synonyms in the Principal Indo-European Languages - Weeks, David Michael (1985)
Ph.D. Dissertation; 1949; Chair: Jaan Puhvel. Order No. DA8522355, cf. DissAbstr 46/08 (February 1986) 2279-A/2280-A.